2018
DOI: 10.1371/journal.pone.0187745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a psychological intervention programme on mental stress, coping style and immune function in percutaneous coronary intervention patients

Abstract: PurposeThis study aimed to assess the effects of a psychological intervention programme on the mental stress, coping style and cortisol and IL-2 levels of patients undergoing percutaneous coronary intervention (PCI).MethodsA total of sixty cardiovascular patients scheduled for PCI with clear anxiety and depression screened by the Hospital Anxiety and Depression Scale were randomly divided into an experimental (n = 30) and control (n = 30) group. The participants in the experimental group received cognitive the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…On account of high risk of stroke, severe complications, or even sudden death, most CAD patients experience helplessness, hopelessness, or worthlessness, resulting in self-reproaches and grave fear, thereby directly increasing occurrences of anxiety and depression (Benjamin et al, 2018; Fakhr-Movahedi et al, 2015; Mozaffarian et al, 2016; Pelletier et al, 2015). Care intervention programs with one or two intervention measures have been broadly utilized in cardiovascular patients for the purposes of psychological management and prognosis improvement (Fakhr-Movahedi et al, 2015; Pedersen et al, 2015; Shen et al, 2018). For instance, a previous study reveals that patients’ education for 5 days contributes to anxiety and depression level reductions in CAD patients by increasing the patients’ awareness of disease risk factors, disease progression, or therapeutic interventions (Fakhr-Movahedi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On account of high risk of stroke, severe complications, or even sudden death, most CAD patients experience helplessness, hopelessness, or worthlessness, resulting in self-reproaches and grave fear, thereby directly increasing occurrences of anxiety and depression (Benjamin et al, 2018; Fakhr-Movahedi et al, 2015; Mozaffarian et al, 2016; Pelletier et al, 2015). Care intervention programs with one or two intervention measures have been broadly utilized in cardiovascular patients for the purposes of psychological management and prognosis improvement (Fakhr-Movahedi et al, 2015; Pedersen et al, 2015; Shen et al, 2018). For instance, a previous study reveals that patients’ education for 5 days contributes to anxiety and depression level reductions in CAD patients by increasing the patients’ awareness of disease risk factors, disease progression, or therapeutic interventions (Fakhr-Movahedi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The variables of age, sex, marital status, education level, income, endovascular stents, comorbidities, and smoking were the adjusted variables in the multivariate Cox model. For all analyses, missing data were transformed by mean imputation[28]. Throughout the analysis, a p-value of less than 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study (2018) used relaxation therapy as one of three psychological intervention programs to assess the effects on mental stress and coping style. This relaxation therapy encompassed: progressive muscle relaxation (PMR), mediation, though guidance, deep breathing and massage [36]. Results revealed that participants in the intervention program improved mental state, reduced negative coping style and showed lower levels of anxiety [36].…”
Section: Relaxationmentioning
confidence: 99%
“…This relaxation therapy encompassed: progressive muscle relaxation (PMR), mediation, though guidance, deep breathing and massage [36]. Results revealed that participants in the intervention program improved mental state, reduced negative coping style and showed lower levels of anxiety [36]. Moreover, Orlick and Partington identified breathing techniques and PMR as two of the most efficient strategies to increase performance [8].…”
Section: Relaxationmentioning
confidence: 99%
See 1 more Smart Citation